The Influence of Learning Facilities and Learning Motivation on Students' Economic Learning Outcomes Class XI SMA Negeri 3 Pematang Siantar - Vonny Maria Pasaribu; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of learning facilities and student learning motivation in class XI economics subjects at SMA Negeri 3 Pematang Siantar. The variables in this research are learning facilities and learning motivation as independent variables and learning outcomes as the dependent variable. This type of research is quantitative research with a quantitative descriptive data analysis approach, with the research population being all students of class XI IPS SMA Negeri 3 Pematang Siantar and the research sample is also all students of class sampling (saturated sampling). The data collection technique uses instruments: (1) learning facilities questionnaire, (2) learning motivation questionnaire, and (3) learning outcomes in the form of daily economics test scores. The results of this research show that: (1) there is a positive and significant influence of learning facilities on learning outcomes, this result can be seen in the t test where the calculated t value of learning facilities (7.123) > t table value (1.65776) which means that this variable significant. (2) there is a positive and significant influence of learning motivation on learning outcomes (2.48) > t table value (1.65776) which means this variable is significant. (3) Learning facilities and learning motivation together influence learning outcomes, this result can be seen in the F test where the calculated F value (25.366) is > compared to the table F value (3.07). The R Square coefficient of determination test was found to be 0.299, meaning that 29.9% of the variables of learning facilities and learning motivation had an influence on student learning outcomes at SMA Negeri 3 Pematang Siantar and the remaining 70.1% was the influence of other variables not examined in this research.